PERBANDINGAN EFEKTIVITAS SILVER SULFADIAZINE DAN MADU DALAM PENYEMBUHAN LUKA BAKAR - Putri, Indrani Nur Winarno (Essential: Essence of Scientific Medical Journal, 2019)
Introduction: Burns caused by heat, radiation, electricity, and chemical exposure. Because of the high of mortality and morbidity on this cases, treatments should be concern. Prevalences of burns in Indonesia are 0,7% and the highest risk are children. Discussion: Dressing Silver sulfadiazine (SSD) is baku emas in management burn healing wound. However SSD can delay burn wound healing and increase scar hypertrophy formation. Honey has antiinflamatory, antibacterial effect, and accelerate burn wound healing, so that scar hypertrophy become smaller. Conclusion: Based on some study, dressing honey give better effect than dressing Silver sulfadiazine in burn wound healing.